Predicting fitness coaches’ intentions to include persons with disabilities in gyms: an application of the theory of planned behavior - Dransmann, Milan; Braksiek, Michael; Meier, Christopher; Gröben, Bernd; Lesch, Lara; Wicker, Pamela (Frontiers in Sports and Active Living, 2025)
IntroductionPromoting equal access to fitness offers implies the inclusion of individuals with disabilities in gyms. However, many gyms do not meet the needs of people with disabilities due to physical, social, and human resource barriers. This study examines fitness coaches’ capacities and intentions of providing fitness offers for individuals with disabilities using the theory of planned behavior as a framework.MethodsA quantitative online survey was conducted with 182 fitness coaches in Germany. The data were analyzed using confirmatory factor analysis, structural equation modeling, and regression analysis to empirically test the theory of planned behavior constructs and identify factors influencing coaches’ intentions.ResultsThe analysis confirmed that descriptive norms and experiential attitudes predict coaches’ intentions to support individuals with disabilities, highlighting the importance of social pressures and experience-based attitudes. Previous experiences, frequent contact with individuals with disabilities, and adequate preparation, often achieved through informal means, play crucial roles in shaping these intention-forming factors.DiscussionAlthough fitness coaches express strong intentions to support individuals with disabilities, there is a need for targeted training and resources. These trainings and additional resources could equip coaches with the necessary skills and knowledge to effectively translate their intentions into practice, even though the actual implementation was not measured in the study.